Message - Al-Shamahy, Prof. Dr. Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2021)
Prof. Dr. Kaijian HouShantou from traditional Chinese medical hospital, in China says in volume 1 – issue 1 of the Universal Journal of Pharmaceutical Research (UJPR) 6 years ago in his prophecy (Editorial Message) "I am pleased to announce the publication of the inaugural issue of UJPR International, peer-reviewed, and open access on behalf of the editorial board. We anticipate great success for the journal in the near future". Dr. Kaijian HouShantou predicted this because of his confidence at that time in himself and the journal staff - as for me, the UJPR has opened the horizons of medical research and publishing for me and I believe to Yemenis from those I know and I assure that our beloved journal has achieved great success in career and we expect a distinguished and great success for the journal in the near future by registering it in Scopus. In addition, One of the evidence of our journal success is that UJPR records indicate that the number of publishers in our journal is increasing and they are the real wealth of the journal and we must share with them their ideas and perceptions to develop the journal . At the end of this short message we need to ask the question "How can we best serve the medical and pharmaceutical sciences and researchers in this field?". The answer to this question is to make more efforts by the editorial board and authors and to maintain a positive attitude and not allow any circumstances or people to stop our progress.